GENERATOR SYNCHRONIZATION PROCEDURE IN A PARALLEL SYSTEM TO SUPPORT SHIP ELECTRICAL SYSTEM PERFORMANCE - Humaira Pelagia; Elkana Bilak Lopo; Lukman Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Generator synchronization is an essential process in ship electrical power systems to ensure continuous power supply, stable operation, and balanced load sharing among generators operating in parallel. Failure to perform synchronization properly may result in electrical disturbances, equipment damage, and interruption of ship operations. This study aims to analyze the implementation of generator synchronization procedures and identify factors affecting synchronization performance on board KM Sabuk Nusantara 108.This research employed a qualitative descriptive approach. Data were collected through direct observation of generator synchronization activities, interviews with engine department personnel, documentation studies, and operational data review. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques.The results indicate that generator synchronization was conducted according to the standard procedure, including inspection of generator condition, voltage matching, frequency matching, phase sequence verification, phase angle adjustment, synchronization monitoring using a synchroscope, and circuit breaker closing. The study also revealed that governor potentiometer instability and contaminated fuel were the dominant factors affecting synchronization performance. Governor disturbances caused frequency fluctuations, while poor fuel quality resulted in unstable diesel engine combustion, leading to difficulties in achieving synchronization conditions. Proper implementation of synchronization procedures contributed significantly to system reliability through balanced load sharing, frequency stability, voltage stability, and uninterrupted electrical power supply.